1999
DOI: 10.1161/01.cir.99.14.1843
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sustained Ventricular Tachycardia Inducible by Programmed Stimulation in Patients With Coronary Artery Disease

Abstract: Background-Cardiologists often use clinical variables to determine the need for electrophysiological studies to stratify patients for risk of sudden death. It is not clear whether this is rational in patients with coronary artery disease, left ventricular dysfunction, and nonsustained ventricular tachycardia. Methods and Results-We analyzed the first 1721 patients enrolled in the Multicenter UnSustained Tachycardia Trial to determine whether clinical variables could predict which patients would have inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…ACE-I ϭ angiotensin-converting enzyme inhibitor; CHF ϭ congestive heart failure; EPS ϭ electrophysiologic study; HTN ϭ hypertension; LV ϭ left ventricle; MI ϭ myocardial infarction; NSVT ϭ nonsustained ventricular tachycardia; PTCA ϭ percutaneous transluminal coronary angioplasty; SA ϭ surface area; VF ϭ ventricular fibrillation; VT ϭ ventricular tachycardia; WMA ϭ wall motion abnormality. mans, limited information suggests that infarct size, as measured by LVEF, maximum creatine kinase, and the number of fixed thallium defects, is related to induction of ventricular arrhythmias (1,(27)(28)(29)(30)(31). Based on autopsy findings, Bolick et al (4) reported that patients with clinical VT after myocardial infarction had larger infarcts than those without.…”
Section: Discussionmentioning
confidence: 99%
“…ACE-I ϭ angiotensin-converting enzyme inhibitor; CHF ϭ congestive heart failure; EPS ϭ electrophysiologic study; HTN ϭ hypertension; LV ϭ left ventricle; MI ϭ myocardial infarction; NSVT ϭ nonsustained ventricular tachycardia; PTCA ϭ percutaneous transluminal coronary angioplasty; SA ϭ surface area; VF ϭ ventricular fibrillation; VT ϭ ventricular tachycardia; WMA ϭ wall motion abnormality. mans, limited information suggests that infarct size, as measured by LVEF, maximum creatine kinase, and the number of fixed thallium defects, is related to induction of ventricular arrhythmias (1,(27)(28)(29)(30)(31). Based on autopsy findings, Bolick et al (4) reported that patients with clinical VT after myocardial infarction had larger infarcts than those without.…”
Section: Discussionmentioning
confidence: 99%
“…In the Multicenter Unsustained Tachycardia Trial population of patients with coronary artery disease, left ventricular ejection fraction of <40 %, and asymptomatic nonsustained ventricular arrhythmia, women were significantly less likely to have inducible ventricular tachycardia compared to men [50]. The decreased risk of ventricular arrhythmias in women with ischemic cardiomyopathy and heart failure has raised questions as to whether the substrate for life-threatening ventricular arrhythmias in women differs enough to warrant withholding ICD therapy [51,52].…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%
“…There are few data comparing the incidence of sustained arrhythmia between men and women, and existing studies have been limited to survivors of cardiac arrest (5)(6)(7)(8). Gender differences have been noted in inducibility of ventricular arrhythmias among patients with CAD (9,10) and in frequency of nonsustained ventricular tachycardia (VT) in patients with congestive heart failure (11), suggesting that men may have greater propensity to ventricular arrhythmia.…”
mentioning
confidence: 99%